2007
DOI: 10.1111/j.1365-2648.2007.04449.x
|View full text |Cite
|
Sign up to set email alerts
|

New midwifery? A qualitative analysis of midwives’ decision‐making strategies

Abstract: Managers need to question whether the strategies they adopt hinder or support clinicians in their efforts to involve women in decisions. Clinicians need to consider whether they wish to be selective or universal in their use of new professional strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…For many of them, this was not consistent, a finding similar to that reported by Porter et al (2007) in their study of midwives' professional behaviour with respect to decision-making. In the study reported here, the midwives' professional identity, as demonstrated by their discursive practices, altered with areas of care.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…For many of them, this was not consistent, a finding similar to that reported by Porter et al (2007) in their study of midwives' professional behaviour with respect to decision-making. In the study reported here, the midwives' professional identity, as demonstrated by their discursive practices, altered with areas of care.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, midwives as NHS employees are commonly constrained by practice guidelines based on medical or managerial, rather than midwifery, principles and priorities (Jowitt, 2001;Porter et al, 2007;Ali, 2008). However, UK midwives have a statutory duty to support women's choices regarding how and where they give birth, and to promote the midwifery approach to birth (Nursing and Midwifery Council (NMC), 2004).…”
Section: Maternity Care and Midwiferymentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies reflect the idea of an underpinning managerial discourse influencing approaches to care of the pregnant woman seeking asylum, with a reliance on policies and guidelines (Nabb, 2006;Reynolds and White, 2010). This also extends to pregnant women more generally (Smith et al, 2009;Porter et al, 2007). In addition, there appears to be a lack of consensus in the literature around whether to approach care from an individual perspective (Schott andHenley, 1996b, Cowan andNorman, 2006) or if it is important to consider a person's context when making care decisions (Nairn et al, 2004;Squire and James, 2009).…”
Section: Discussionmentioning
confidence: 99%